The Archeological Museum of Pasca: a Hypothesis about its Origin - Díaz Jaramillo, José Abelardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article inquires into the origin of the ArcheologicalMuseum of Pasca (MAP), argumenting that its creationresponds to a sociocultural strategy designed by the parishpriest Jaime Hincapié Santamaría in order to strengthenrelations between the community and the parish. This tookplace in a local context marked by agrarian conflicts, which,by means of a long process, configured a political foundationof liberal and communist ideas among its inhabitants. Whatis singular about this parish priest´s interest, as this articleaims to demonstrate, is that this effort was not accompaniedby religious discourse, but by a domesticated revindicationof the indigenous local past. For this purpose, this articleuses a strategy that articulates historical knowledge on thelocal context in which MAP emerged and on the life of JaimeHincapié Santamaría, with testimonies of the inhabitants ofthe municipality, which allowed identification of the meaningsgiven to this museum. In this way, this exercise will allowthe historization of a place of memory of the Sumapaz regiónof Colombia, highlighting the role of priests as socioculturalagents.